STRUGGLES IN SUZANNE COLLINS’ NOVEL THE HUNGER GAMES - Intan Novia Sari; Purwarno Purwarno (Universitas Islam Sumatera Utara, 2019)
This research is the result of qualitative research on the protagonist’s struggles named Katniss Everdeen depicted in Suzanne Collins’ novel The Hunger Games. Burleson (1964) says that struggle is one of ways to reach the better life in the future and also to increase the prestige. It means that any hope will be achieved through struggling. Katniss Everdeen is a strong as well as a resourceful sixteen-year-old girl who is far more mature than her age would suggest. Katniss is the main provider in her family, which consists of Katniss, her mother, and her younger sister, Prim Everdeen. She must struggle hard to make herself and her family stay life. Therefore she always keeps on struggling in her life. The finding of this research shows that the protagonist is succesful in her struggles to fulfill her family needs, to protect her sister and to win in the Hunger Games.